COCHLEAR SYNAPTIC TINNITUS – CAN IT BE CURED - SOWMYA, RAMARAPPU; MAHESH, DASARI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to determine the tinnitus demography, etiology, treatment options, and their response in a Tertiary Care Teaching Hospital. Methods: The study was conducted on patients above 21 and below 80 years who presented with tinnitus and hearing loss to ENT outpatient department (OPD) of Dr. Patnam Mahender Reddy Institute of Medical Sciences (PMRIMS), Chevella from May 2019 to February 2020. To identify the cause of tinnitus, the following investigations were considered: Pure-tone audiogram; tympanometry; blood investigations, color Doppler ultrasonography to evaluate blood flow disturbance in the vertebral and basilar artery, middle/inner ear high-resolution computerized tomography scan (CT), and, in the case of suspicion of vestibular Schwannoma or neurovascular conflict, magnetic resonance imaging/angio-CT (MRI/Angio-CT) was done. Results: Among the patients attending ENT OPD with tinnitus, those with idiopathic cochlear synaptic tinnitus were identified, and 100 were selected and treated with various modalities of pharmacological treatment available for the same found that no specific drug was 100% effective in relieving the symptom. Conclusion: The present study treated tinnitus of cochlear origin with various drugs and followed up with patients for 3 months. They were assessed with tinnitus sample case history questionnaire, and the study concluded that no pharmacological treatment effectively treats cochlear synaptic tinnitus.